RESPONS PRODUKSI TERHADAP JARAK TANAM SALAK PANGU DI DESA PANGU RAYA KECAMATAN RATAHAN TIMUR NORTH SULAWESI INDONESIA - Franky Reintje Tulungen; Vini N. Ngantung; Jemly Lengkong (AGRI-SOSIOEKONOMI, 2020)
This study aims to obtain the plant spacing of salak-pangu on sloping land which gives high yields. This study held on January until June 2020 with survey method and data collection techniques using structured interviews with 28 salak-pangu farmers in Pangu Raya village and field observations. The samples of this study were purposively. The variables in this study were the plant spacing of salak-pangu (X) and the plant production of salak pangu per hectare (Y). The collected data were analyzed descriptively followed by the t-test to determine the plant spacing that gave high production. The result shows that plant spacing affects the production of salak-pangu per ha. The production response forms a production function curve with the plant spacing of salak-pangu that gives the highest yields production is 1x3 meter spacing.*eprm*